Literature review: Prinsip dasar anestesi pada pasien eklampsia - Hidayat, Lujna Adharani; Sommeng, Faisal; Aman, Abadi; Rakhmah, Nur; Hasir, Julia (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Eclampsia is a life-threatening obstetric complication associated with high maternal and perinatal morbidity and mortality. Anesthetic management in eclampsia is challenging due to endothelial dysfunction, severe hypertension, seizure risk, and systemic complications affecting maternal and fetal outcomes. Objective: To review and summarize the basic principles of anesthetic management in patients with eclampsia based on current scientific evidence. Methods: This study employed a narrative literature review approach. Data were obtained from electronic databases including PubMed, ScienceDirect, Google Scholar, and Cochrane Library. Included studies were published in English and Indonesian, focusing on eclampsia and anesthetic management, with study designs such as systematic reviews, meta-analyses, cohort studies, and case reports. Literature selection followed inclusion–exclusion criteria and PRISMA guidelines. Results: The main principles of anesthetic management in eclampsia include initial stabilization (ABCDE), seizure control with magnesium sulfate, gradual blood pressure control, and restrictive fluid management. The choice of anesthetic technique should be individualized; regional anesthesia is preferred in stable patients without coagulopathy, while general anesthesia is indicated in emergency situations or when regional anesthesia is contraindicated. Close intraoperative monitoring and intensive postoperative care are essential to prevent complications. Conclusion: Anesthetic management in eclampsia requires a comprehensive and individualized approach.   Keywords: Eclampsia; Obstetric Anesthesia; Magnesium Sulfate; Hypertensive Disorders Of Pregnancy; Perioperative Management.   Pendahuluan: Eklampsia merupakan komplikasi obstetri yang mengancam jiwa dengan morbiditas dan mortalitas maternal serta perinatal yang tinggi. Penatalaksanaan anestesi pada pasien eklampsia menjadi tantangan karena adanya disfungsi endotel, hipertensi berat, risiko kejang, serta komplikasi sistemik yang dapat memengaruhi outcome ibu dan janin. Tujuan: Meninjau dan merangkum prinsip dasar manajemen anestesi pada pasien eklampsia berdasarkan bukti ilmiah terkini. Metode: Penelitian ini menggunakan metode literature review dengan pendekatan naratif. Data diperoleh dari berbagai basis data elektronik seperti PubMed, ScienceDirect, Google Scholar, dan Cochrane Library. Artikel yang disertakan adalah penelitian dalam bahasa Inggris dan Indonesia yang membahas eklampsia dan manajemen anestesi, dengan desain studi seperti systematic review, meta-analisis, cohort, dan laporan kasus. Seleksi literatur dilakukan berdasarkan kriteria inklusi dan eksklusi serta mengikuti pedoman PRISMA. Hasil: Prinsip utama manajemen anestesi pada eklampsia meliputi stabilisasi awal (ABCDE), kontrol kejang menggunakan magnesium sulfat, pengendalian tekanan darah secara bertahap, serta manajemen cairan yang restriktif. Pemilihan teknik anestesi harus individual; anestesi regional lebih disarankan pada pasien stabil tanpa gangguan koagulasi, sedangkan anestesi umum digunakan pada kondisi emergensi atau kontraindikasi regional. Monitoring intraoperatif dan perawatan pascaoperatif yang ketat berperan penting dalam mencegah komplikasi. Simpulan: Manajemen anestesi pada pasien eklampsia memerlukan pendekatan komprehensif dan individualisasi berdasarkan kondisi klinis pasien.   Kata Kunci: Anestesi Obstetri; Eklampsia; Magnesium Sulfat; Hipertensi Kehamilan; Manajemen Perioperatif.